I've Got the Power. - Jones, W.D.
Southwest Wind Power, a start-up located in Flagstaff, AZ, has developed an affordable turbine that matches the efficiency of commercial wind farm turbines and produces power at grid prices. Dubbed SkyStream, the 1.8-kilowatt residential wind turbine is capable of trimming home electricity bills by 20 to 90%, depending on wind velocities, electricity prices, and government incentives in a particular area. A result of the US Department of Energy's Wind Energy Program, Sky Stream can produce about 100,000 kWh of power during its 20-year design life. Abble to outperform 50- to 100-kW machines in terms of average cost of energy, its sales potential is very promising
Keywords: 1.8 kW; 50 to 100 kW; Arizona; Dubbed SkyStream; Flagstaff; Southwest Wind Power; US Department of Energy; Wind Energy Program; Commercial wind farm; Electricity prices; Government incentives; Home electricity bills trimming; Residential wind turbine; Wind velocities